PENGARUH BEBERAPA KEHALUSAN TEPUNG BATUAN ANDESIT DAN PENGEKSTRAK TERHADAP KETERSEDIAAN HARA ULTISOL - Richard Alex Stepanus; Bintang Bintang; Jamil Jamilah (Universitas Sumatera Utara, 2014)
Soil has suffered impoverishment nutrient in many place, meanwhile igneous rocks such as andesitein Indonesia still underutilized. Therefore, the research had been conducted to testing the ability ofandesite rock dust on some fineness with the provision of extractors to increasing nutrientsavailability. It had been conducted at the greenhouse, College of Agriculture, North SumatraUniversity, Medan using factorial randomized completely design with two factors and threereplicates, i.e. fineness (80, 40, and 20 mesh) and extractors (distilled water, cow urine, pineapplejuice, and peat water). Parameters analyzed were soil reaction (pH H2O), P-available, exchangebases (K, Na, Ca, and Mg), CEC, and base saturation. The result showed that the fineness ofandesite rock dust increased pH H2O and K-exchange, but couldn’t improve P-available, Naexchange,Mg-exchange, CEC, and base saturation.The extractors increased pH H2O, K-exchange, Mg-exchange, and base saturation, but couldn’timprove P-available, Na-exchange, Ca-exchange, and CEC. Interaction between two treatmentscouldn’t improve and didn’t increase ultisol nutrients availability.________________________________________________________________________________Keywords: Andesite rock dust, fineness, extractors, nutrients availability